Agricultural Policy in Russia: Global Challenges and the Viability of Rural Communities - Kalugina, Zemfira I. (The International Journal of Sociology of Agriculture and Food, 2014)
The evolution of agricultural policy in Russia under the influence of external and internal challenges from the market reforms of the 1990s and ending with the entry of Russia into the WTO in 2012 has been a difficult one. The article presents an analysis of institutional traps, and of the measures and strategies that are employed to try to overcome them. The results of the market reforms of the Russian agricultural sector are assessed from an economic and social point of view, identifying the dominant survival strategies of rural communities in the diversification of the rural economy and rural employment. In conclusion, the author tries to answer the question why privatization and market reforms have not succeeded within the agricultural sector, and the reasons for the prevailing farming alternatives. The analysis and reflections are based on data from sociological surveys and government statistics as well as a number of research visits and interviews in rural regions of Russia over several decades.